2020
DOI: 10.1038/s41598-020-59911-6
|View full text |Cite
|
Sign up to set email alerts
|

The effects of NMDA receptor blockade on TMS-evoked EEG potentials from prefrontal and parietal cortex

Abstract: Measuring the brain's response to transcranial magnetic stimulation (TMS) with electroencephalography (EEG) offers unique insights into the cortical circuits activated following stimulation, particularly in non-motor regions where less is known about TMS physiology. However, the mechanisms underlying TMS-evoked EEG potentials (TEPs) remain largely unknown. We assessed TEP sensitivity to changes in excitatory neurotransmission mediated by n-methyl-d-aspartate (NMDA) receptors following stimulation of non-motor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 60 publications
2
25
0
Order By: Relevance
“…A consensus on the best pre-processing pipeline has yet to be reached [ 1 ]; thus, we deemed it important to collect data about different pre-processing solutions. There are two main reasons why the two pipelines could have yielded different results, as in previous work [ 24 , 36 ]. The first pertains to the EEG artefact that is caused by scalp muscle activation, which is handled differently by SSP-SIR and ICA.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A consensus on the best pre-processing pipeline has yet to be reached [ 1 ]; thus, we deemed it important to collect data about different pre-processing solutions. There are two main reasons why the two pipelines could have yielded different results, as in previous work [ 24 , 36 ]. The first pertains to the EEG artefact that is caused by scalp muscle activation, which is handled differently by SSP-SIR and ICA.…”
Section: Discussionmentioning
confidence: 98%
“…Subsequently, the signals were down-sampled to 1000 Hz, band-pass (1–100 Hz) and band-stop (48–52 Hz) filtered with a fourth order Butterworth filter. The epochs were restricted to (−1 to 1 s) in order to reduce possible edge artefacts, and a round of SOUND (source-estimate-utilizing noise-discarding algorithm) [ 23 ] was applied to further clean the signal (λ = 0.1, 20 iterations), as previously done with TMS-EEG data [ 24 ]. A second round of fastICA was then performed, plotting the full epoch length, to remove residual artefacts non time-locked with the TMS pulse (e.g., spontaneous eyeblinks and continuous muscle activity).…”
Section: Methodsmentioning
confidence: 99%
“…Most of the studies on DLPFC stimulation agree on deflections such as the N40, P60, N100 and P185 (Bagattini et al, 2019;Chung et al, 2019;Conde et al, 2019;Gordon et al, 2018;Rogasch et al, 2014;Voineskos et al, 2019), but other peaks are often reported at ~30 ms, ~50 ms, or ~70 ms (Bagattini et al, 2019;Conde et al, 2019;Rogasch et al, 2014). For IPL, there is still little characterization of TEP components and the few studies that reported them have shown inconsistent results (Conde et al, 2019;Rogasch et al, 2020;Romero Lauro et al, 2014). According to our findings, the preprocessing phase could be a possible source of variability in TEPs' earlycomponent (<100 ms) definition.…”
Section: Variability Brought By the Choice Of The Preprocessing Pipelmentioning
confidence: 99%
“…Therefore, we studied the spatiotemporal distribution of TEPs during the stimulation of the temporo-occipital cortex (TOC) and the DLPFC of both hemispheres. Although there is still uncertainty regarding late deflections (>80 ms), early TEPs (<80 ms) are more widely recognized to reflect activity of the stimulated cortex ( Herring et al, 2015 ; Du et al, 2017 ; Conde et al, 2019 ; Rogasch et al, 2020 ). We thus focused on late negative deflections corresponding to the N100 in motor cortex stimulation and expected to identify lateralized site-specific components over the stimulated brain region.…”
Section: Introductionmentioning
confidence: 99%